(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2023)
Cucumber downy mildew is a typical fungal airborne disease in which pathogenic spores are transmitted remotely by air currents, resulting in regional endemics. It is of great significance to study and analyze the temporal and spatial changes of downy mildew spores, especially the trajectory and sedimentation concentration of spores propagating with airflow in the air, for the prediction of downy mildew in cucumbers. Therefore, based on GDAS meteorological data from October to November 2017, this study uses the HYSPLIT-5 model to simulate the airflow propagation trajectory and sedimentation of downy mildew pathogen spores in the main cucumber planting areas in China, analyzes the trajectory frequency and sedimentation concentration in the long-distance and long-term series propagation process, and explores the transmission law of airborne disease spores, which provides a theoretical basis for predicting downy mildew in cucumbers.